The Evaluation of rambutan (Nephelium lappaceum) accessions for yield and fruit quality - AWACHARE, CHANDRAKANT M; TRIPATHI, P C; KARUNAKARAN, G; SAKTHIVEL, T; SENTHILKUMAR, R; RAJENDIRAN, S; MURALIDHARA, B M; MURTHY, B N S (The Indian Journal of Agricultural Sciences, 2022)
Ten promising accessions of rambutan were evaluated for five years (2017–21) to study the differences for selected horticultural traits. The accessions studied differed significantly with respect to tree growth, yield and fruit quality. The fruiting density was maximum in Arka Coorg Peetabh followed by CHES-R-26 and Arka Coorg Arun. Similarly, Arka Coorg Peetabh also recorded significantly higher fruit yield, yield efficiency and average fruit weight as compared with other accessions studied. The accession CHES-R-26 excelled in fruit quality variables (total soluble solids, titratable acidity and ascorbic acid content) as compared with Arka Coorg Peetabh and Arka Coorg Arun. Further, three accessions (CHES-R-I-3, CHES-R-III-9 and CHES-R-III-4) were also found superior in terms of yield and fruit quality. The results on vegetative growth parameters indicated that the accessions, viz. CHES-R-I/1, Arka Coorg Arun, CHES-R-26 and CHES-R-III/9 were found to be vigorous for tree spread and canopy volume. These variations among accessions studied may prove relevant in selecting or breeding new cultivars in rambutan.